Rasisme di Media Sosial: Studi Tafsir Al-Munir Karangan Wahbah Az-Zuhaili Q.S. Al-Hujurat Ayat 11-13 - Azharani Filza; Adenan; Agusman Damanik (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Racism often occurs in everyday life and on social media. Many social media users deliberately post hateful comments to insult others, often related to racism, such as discriminatory treatment based on skin color. This issue contradicts the teachings of the Quran, which advocates tolerance, harmony, and politeness. This research uses a qualitative method with a literature study approach, referring to Wahbah Az Zuhaili's Tafsir Al Munir to analyze the issue of racism in Q.S. Al Hujurat verses 11-13. Wahbah Az Zuhaili interprets these verses based on his experiences and intellectual background, emphasizing the prohibition of insulting, belittling, and finding fault with others, and highlighting the principle of human equality, distinguished only by piety and character. The divine system in mentioning ethics includes reports about corrupt people, the impact of conflict, the prohibition of despicable behavior, and the affirmation of the unity of mankind, with the aim of maintaining the unity of Muslims and spreading the teachings of Islam at all times and places.